Primary HBB gene mutation severity and long‐term outcomes in a global cohort of β‐thalassaemia. (25th October 2021) - Musallam, Khaled M.; Vitrano, Angela; Meloni, Antonella; Addario Pollina, Sebastiano; Di Marco, Vito; Hussain Ansari, Saqib; Filosa, Aldo; Ricchi, Paolo; Ceci, Adriana; Daar, Shahina; Vlachaki, Efthymia; Singer, Sylvia T.; et al.
Summary: In β‐thalassaemia, the severity of inherited β‐globin gene mutations determines the severity of the clinical phenotype at presentation and subsequent transfusion requirements. However, data on associated long‐term outcomes remain limited. We analysed data from 2109 β‐thalassaemia patients with available genotypes in a global database. Genotype severity was grouped as β 0 /β 0, β 0 /β +, β + /β +, β 0 /β ++, β + /β ++, and β ++ /β ++ . Patients were followed from birth until death or loss to follow‐up. The median follow‐up time was 34·1 years. Mortality and multiple morbidity outcomes were analyzed through five different stratification models of genotype severity groups. Interestingly, β 0 and β + mutations showed similar risk profiles. Upon adjustment for demographics and receipt of conventional therapy, patients with β 0 /β 0, β 0 /β +, or β + /β + had a 2·104‐increased risk of death [95% confidence interval (CI): 1·176–3·763, P  = 0·011] and 2·956‐increased odds of multiple morbidity (95% CI: 2·310–3·784, P  < 0·001) compared to patients in lower genotype severity groups. Cumulative survival estimates by age 65 years were 36·8% for this subgroup compared with 90·2% for patients in lower genotype severity groups ( P  < 0·001). Our study identified mortality and morbidity risk estimates across various genotype severity groups in patients with β‐thalassaemia and suggests inclusion of both β + and β 0 mutations in strata of greatest severity.